Interaction of heparin with cationic molecular probes: probe charge is a major determinant of binding stoichiometry and affinity - Szelke, Helga; Schübel, Sarah; Harenberg, Job; Krämer, Roland (Bioorganic & medicinal chemistry letters, 2010)
Fluorescent perylenediimide probes modified with 2, 4, 6, or 8 ammonium groups were synthesized and their binding to the antithrombotic drug heparin was studied by fluorescence spectroscopy in solution. The polyanionic polysaccharide strands of heparin bind more probe molecules per sugar unit when the charge of the latter is low, and stability of the probe-heparin complex increases with increasing probe charge.
Gesehen am 08.09.2023